Construction Characteristics and Quality Control Measures Under High Altitude and Cold Conditions. Issue 1 (February 2021) - Yang, Junpeng; Li, Minyan
Abstract: Restricted by the natural environment factors, the high altitude and cold regions have low air pressure, low air density, large temperature difference between day and night, and long freezing and cold time. During the construction, strict requirements are put forward for the material preparation, material transportation, construction machinery, construction technology, workers' personal safety and other aspects. Based on the engineering construction in Tibet, this paper studies the optimization scheme of concrete mix proportion and the systematic insulation measures of concrete construction in high altitude and cold regions. The influence of ultra-low temperature on metal welding process is studied. The effects of welding wire selection, welding environment guarantee and worker training on welding quality assurance are studied. The calculation method of mechanical efficiency reduction and the influence of altitude on environmental factors and quota adjustment coefficient are studied. The results of this study provide reference and technical support for the construction in high altitude and cold areas.